Social Norms and Optimal Incentives in Firms - Steffen Huck; Dorothea Kübler; Jörgen Weibull (The Research Institute of Industrial Economics (IUI), 2001)
This paper deals with the interplay between economic incentives and social norms in firms. We outline a simple model of team production and provide preliminary results on linear incentive schemes in the presence of a social norm that may cause multiple equilibria. The effect of the social norm on the optimal bonus rate is discussed, as well as the effectiveness of temporary changes in the bonus rate as a means to move a firm from a bad to a good equilibrium.
Keywords: D23; 330; Social Norms; Incentives; Contracts; Leistungsanreiz; Leistungsentgelt; Theorie; Soziale Norm